Effect of Work Discipline, Training, Work Supervision on Employee Job Satisfaction at PTPN III - Ruth Sahana; Honesty Selviani Laoli; Putri Srimenggar Situmorang; Toni Joshua Hutabarat; Kristi Endah Ndilosa Ginting (Journal of Research in Business, Economics, and Education, 2022)
This study aims to examine and analyze the effect of discipline, training, supervision, on job satisfaction at PTPN III. In supporting job satisfaction, the company provides several benefits such as salary, bonuses, allowances, THR, leave money, premium school children assistance, overtime and facilities such as houses for those who work in plantations or factories and BPJS. In terms of discipline, the level of employee absenteeism is still high and there are still employees who arrive late and leave work early, this indicates that employees are still lacking discipline in terms of attendance. The training is carried out so that the ability of employees will increase, this will certainly add to the insight of employees and lead to new initiatives to achieve the goals of an agency. In supervision, the Covid 19 pandemic has resulted in employees working from home (work from home) so that companies cannot carry out effective supervision directly on employees. This study uses quantitative research with the research population is all employees of PTPTN III totaling 683 people with the sample used is 253 people. The data analysis method used multiple linear regression. Simple random sampling was used as a sampling method. In the t-test on discipline variables with values ​​(4.240>1.971), training (3.040>1.971) and supervision (4.453>1.971) partially positive and significant effect on job satisfaction at PTPN III. In the F test, the variables of discipline, training, supervision showed a positive and significant influence with a value (30,064>2.67) on job satisfaction at PTPN III